Development of zinc strand continuous casting into a rotor die for anode production - E. F. Baranovsky; V. M. Iljushenko; V. A. Pumpur; G. P. Korotkin; A. I. Kalentionok (Литьë и металлургия, 2001)
The article describes the structure of an experimental setup for a 10 mm zinc strand continuos casting into a mold of a 'wheel-belt” type. The mold cooling parameters, casting modes and results of production tests of zinc anodes out of cast strand are given.